Strategies to streamline the process of integration and implementation of problem-based learning in the medical curriculum. - Shrivastava, Saurabh R.; Bobhate, Prateek S.; Mendhe, Harshal G. (Indian Journal of Community Health)
Acknowledging the complexities and the vastness of the medical curriculum, time and again, the adoption of interactive and innovative teaching-learning methods has been advocated. Problem-based learning (PBL) method is expected to enhance student engagement, support adult learning principles, and assist students in their journey to attain different learning competencies. The PBL method advocates student-centered learning, wherein medical students take responsibility for their individual learning, which is not the case with conventional methods, where students are often passive recipients of the information provided by teachers. In conclusion, the approach of problem-based learning tends to overcome multiple deficiencies of the traditional curriculum and prepares students to effectively discharge their role as effective healthcare professionals. The need of the hour is to systematically plan and involve all the stakeholders in the planning and implementation process to derive the desired benefits.